SUPERVISI PENDIDIKAN OLEH PENGAWAS SEKOLAH - Slameto, Slameto (Kelola: Jurnal Manajemen Pendidikan, 2016)
The problem in this research was related to the effectiveness of supervision programs implemented by the school superintendent and formulated by: 1) What were the steps supervision was conducted by a school supervisor? 2) How were the results of supervision for teachers in improving the quality of education? 3) What were the constraints and any supporting factors faced by school inspectors in carrying out its duties and functions? This study used a study document on the results of previous studies. The data collected by searching through Google Scholar journal. From the search results obtained by 26 then selected to obtain 9 journals which fill in criteria needed. From these 9 journals then conducted a meta-analysis. The results related to measures of supervision performed by school inspectors programmed, structured attention to the vision, mission and goals of partner schools and their regulations: include academic supervision carried out by applying the techniques of individuals and groups. Evaluation results were obtained surveillance program varies, ranging from moderate to attribute positive results. Evaluation of the implementation of supervision was ranged from the low category to very well performance. The evaluations toward the result supervision were also varying from low category, moderate to perform effectively. Constraints faced by school inspectors in carrying out their duties and functions to be involved in external conditions and internal inspectors concerned.